1997
DOI: 10.1038/sj.jhh.1000510
|View full text |Cite
|
Sign up to set email alerts
|

Avoiding the supine position during sleep lowers 24 h blood pressure in obstructive sleep apnea (OSA) patients

Abstract: Obstructive sleep apnea (OSA), is a common clinical inexpensive method for avoiding the supine posture during sleep, namely the tennis ball technique. condition affecting at least 2-4% of the adult population. Hypertension is found in about half of all OSA Of the 13 patients, all had a reduction in 24-h mean BP (MBP). The mean 24-h systolic/diastolic (SBP/DBP) fell by patients, and about one-third of all patients with essential hypertension have OSA. There is growing 6.4/2.9 mm Hg, the mean awake SBP/DBP fell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
1
4

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(31 citation statements)
references
References 12 publications
0
26
1
4
Order By: Relevance
“…Whether any specific antihypertensive drug class has superior blood pressure control in OSA is unclear. Sleep apnea treatments, including positional therapy, 24 oral appliances, 25,26 and bariatric surgery, 27 have been suggested to improve hypertension in OSA patients. Presumably, the primary antihypertensive effect is achieved via relief of concomitant OSA.…”
Section: Managementmentioning
confidence: 99%
“…Whether any specific antihypertensive drug class has superior blood pressure control in OSA is unclear. Sleep apnea treatments, including positional therapy, 24 oral appliances, 25,26 and bariatric surgery, 27 have been suggested to improve hypertension in OSA patients. Presumably, the primary antihypertensive effect is achieved via relief of concomitant OSA.…”
Section: Managementmentioning
confidence: 99%
“…41 The effect on systemic blood pressure of promoting the lateral sleep position for 1 month was studied in 13 patients with OSAHS, six of whom were hypertensive. 42 Mean 24 hour, awake and sleeping blood pressure fell significantly (systolic/diastolic 6.4/2.9, 6.6/3.3, 6.5/2.7 mm Hg, respectively). The reduction in systolic blood pressure was greater in the hypertensive patients than in those who were normotensive.…”
Section: Sleep Positionmentioning
confidence: 89%
“…37 A secondary advantage of positional therapy may be the effect on hypertension that was demonstrated by a small study (n = 13) that showed that sleeping in the nonsupine position lowered the mean blood pressure (BP) in 100% of the study population after 1 month. 38 …”
Section: Sleep Positionmentioning
confidence: 97%